Петро Шелест у контексті політичної історії України ХХ століття - Шаповал, Ю.І. (Український історичний журнал, 2008)
Статтю присвячено одному з найцікавіших українських політиків ХХ століття. Автор аналізує життєвий шлях, особисті риси та політичну лінію П.Шелеста, який очолював ЦК КПУ з 1963 до 1972 р. Він обстоював інтереси України, вимагав дотримання московським керівництвом офіційно декларованих принципів у взаєминах Центру і союзних республік. Це та зусилля політичних конкурентів створили П.Шелесту імідж «надмірного» українського патріота, який нібито плекає плани більшої «автономізації» України. Стаття містить спробу намалювати реалістичний портрет П.Шелеста, деконструювати міфи і стереотипні уявлення щодо нього. The article is dedicated to one of the most interesting Ukrainian politicians of the XX century. The author analyzes creative work, personal features and political tack of P.Shelest, who headed Central Committee of the CPU from 1963 till 1972. He stood for the interests of Ukraine, demanded of Moscow authorities adhering to officially declared principles in relations of the Centre and the Union republics. This and efforts of political rivals produced P.Shelest an image of an «immoderate» Ukrainian patriot, who, according to their words, cherished the plans of a greater «autonomism» of Ukraine. The article contains an attempt to draw P.Shelest’s realistic portrait, deconstruct myths and stereotypical notions about him.